2021
DOI: 10.21608/ejhm.2021.156452
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Ginger Extract and Selenium in theThyroid Gland Toxicity Induced by Chlorpyrifos in Male Albino Rats

Abstract: Background: Chlorpyrifos CPF is one of the organophosphate insecticides that were interfered with the body's hormones. Thyroid hormones are necessary to maintained normal metabolism, growth and development and the disturbance of their levels leads to adverse medical conditions. Ginger extract and selenium are effective antioxidants. Aim of the work: This study examined effect of CPF on the thyroid gland structure and function and the ameliorative effect of ginger extract and selenium. Material and Methods: for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Rats administrated Chlorpyrifos (organophosphate insecticide) and ginger extract at a dose of 750 mg/kg b.w. five days/week for six weeks showed some follicles of the thyroid gland with strong PAS reaction and others with negative PAS reaction (32) .…”
Section: Discussionmentioning
confidence: 97%
“…Rats administrated Chlorpyrifos (organophosphate insecticide) and ginger extract at a dose of 750 mg/kg b.w. five days/week for six weeks showed some follicles of the thyroid gland with strong PAS reaction and others with negative PAS reaction (32) .…”
Section: Discussionmentioning
confidence: 97%
“…12 (2022) results confirmed the present configuration of NaFinduced histologial alterations in thyroid follicles that revealed congestion of blood vessels, hemorrhage, inflammation and decrease in thyroid follicle size. El-Kerdasy et al [55] found thyroid follicle destruction with macrophages infiltration and a significant increase in serum TSH levels, as well as that chlorpyrifos toxic effects on thyroid gland tissue which may be due to lipid peroxidation associated with stellate cell stimulation for collagen synthesis in between thyroid follicles. Abdelaleem et al [8] reported that NaF causes major pathological changes in follicular cells and cellular components, resulting in decreased colloid secretion, as well as that the early reaction of TSH triggered thyroid follicular cells is ingestion of colloid material, which explains decreased luminal colloid.…”
Section: Discussionmentioning
confidence: 99%